Digital geographies of mundane violence: outline of an emerging research field and the example of (cyber-)bullying in young people’s lives - Bork-Hüffer, Tabea; Mahlknecht, Belinda; Markl, Andrea; Kaufmann, Katja (Erdkunde, 2023)
The objective of this article is to outline the emerging field of the “digital geographies of mundane violence”, which is characterised by a critical and reflective engagement with the spatialities and dynamic and non-linear temporalities of mediated violence unfolding in entangled online and offline spaces. Going beyond a conventional review of existing literature, we apply Barad’s (2007: 25) “diffractive methodology” to “read through” findings of studies on violence with non-essentialist concepts of entangled online and offline space and spatiality. Given the variety of technologies, forms of violence, and spaces in which violence unfolds, we develop our argument by focusing on a specific type of gender-based violence: (cyber-)bullying of young people identifying with “abundant identities” (Persson et al. 2020: 67) that neither conform to hegemonic heterosexuality and binary gender categories nor are confined to LGBTQI categories. We discuss the ambivalent role of digital technologies in the negotiation and diffraction of difference by young people facing exclusionary identity politics and violent processes of heteronormalisation and heterosexualisation. We present an illustrative research design from our own work, which combines retrospective insights into biographies, family and social relations and media use with a participant-led, mobile, partly in-situ exploration of everyday entangled mediated experiences, practices and negotiations of inclusion, exclusion and violence. Therewith we outline how the contextualities, dynamics, fluidities, non-linearities and variegated historicities behind mediated violence in entangled online and offline spaces can be empirically unpacked. We show how digital technologies are an intrinsic and entangled part of social, cultural, and political negotiations, discourses, and processes, and contribute significantly to the normalisation and everyday (re-)production of diverse forms of violence.